The Role of Implicature in Promoting SDG 16 Through Preman Pensiun: A Pragmatic Perspective - winarti; Alyssa Nur Rochmah; Beta Setiawati; Feriska Pratiwi (2025)
The research examines how implicatures in the dialogues of the TV series Preman Pensiun function to promote the values of Sustainable Development Goal 16 (SDG 16). This study identifies types of implicature based on violation of the maxim, analyses their implied meanings, and examines how these implicatures support SDG 16. The research employs a qualitative pragmatic approach, focusing on the analysis of conversational implicatures found in selected episodes of Preman Pensiun. Data collection involves transcribing dialogues which are included to implicature by using Grice’s Cooperative Principle and conversational maxims, examining how speakers imply meanings beyond their explicit statements, and categorizing implicatures based on their contribution to SDG 16’s themes. The study finds 25 conversational implicature from episode 1-3 of Preman Pensiun Season 10 that consistently convey messages supporting SDG 16 indicators, namely anti-corruption, peace and security, justice in institution, and inclusiveness and respect. Overall, implicature in Preman Pensiun functions as a pragmatic tool to subtly promote SDG 16 values. By connecting these pragmatic elements to SDG 16, the study shows that television dialogues can do more than entertain. They can also raise awareness about peace, justice, and fair institutions. This research offers a fresh perspective on how language use in everyday media reflects important social values and reveals the potential of popular culture to play a role in supporting global development goals.